2016
DOI: 10.1007/s13201-016-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of textile effluents on microbial diversity in Tirupur district, Tamil Nadu

Abstract: The expedited advent of urbanization and industrialization for economic growth has adversely affected the biological diversity, which is one of the major concerns of the developing countries. Microbes play a crucial role in decontaminating polluted sites and degrades pollution load of textile effluent. The present study was based on identification of microbial diversity along the Noyaal river of Tirupur area. River water samples from industrial and non-industrial sites and effluent samples of before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…The isolated bacterial isolates were presumptively identified and characterized by biochemical tests as Pseudomonas sp., Alcaligenes sp., Bacillus sp., Staphylococcus sp., Enterobacter sp., Escherichia sp., Shigella sp., Salmonella sp., Paenibacillus sp., Micrococcus sp., Klebsiella sp., Proteus sp. and Burkholderia sp., this finding of the present study is consistent with some other previous studies [42][43][44].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The isolated bacterial isolates were presumptively identified and characterized by biochemical tests as Pseudomonas sp., Alcaligenes sp., Bacillus sp., Staphylococcus sp., Enterobacter sp., Escherichia sp., Shigella sp., Salmonella sp., Paenibacillus sp., Micrococcus sp., Klebsiella sp., Proteus sp. and Burkholderia sp., this finding of the present study is consistent with some other previous studies [42][43][44].…”
Section: Discussionsupporting
confidence: 95%
“…The characterization of microbial diversity is the first step for any sort of understanding of a system, either its function or applications [42]. In the present study, 13 different bacterial genera were isolated and identified from the textile dye effluent.…”
Section: Discussionmentioning
confidence: 97%
“…The similarity in the predominant bacteria isolates from effluent and hand-dug wells suggests that the microbial population of the effluent may have impacted the shallow hand-dug wells and the presence of these microbes in the water poses a risk to public health. Moreover, there is a peculiarity in the isolates that constituted predominant organisms in this study, in that they have been well reported by other investigators as being highly adaptive in their capacity to survive in toxic environment such as dye impacted areas (22) , (23) . Their ability to adapt, accumulate and utilize toxic polluting compounds as energy sources had been widely reported.…”
Section: Microbial Load and Bacteria Isolatesmentioning
confidence: 60%
“…Used chemicals in the whole process are discarded as effluent in normal water bodies. These effluents contaminate normal water bodies and affect aquatic life (Prabha et al 2017). Another side, high-dose and long-term exposure of chemicals to any individual/worker may cause many medical disorders such as lung, colorectal, bladder, and breast cancer (Singh and Chadha 2016).…”
Section: Chemicals Used In Textile Industries and Their Hazardous Effectsmentioning
confidence: 99%